Modelado de pérdidas geométricas en sistemas NLOS-UOWC con superficie marina ondulatoria - Samaniego-Rojas, Paulo; Salcedo-Serrano, Pedro; Del Castillo Vázquez, Beatriz; Boluda Ruiz, Rubén; Garrido-Balsells, José María; García Zambrana, Antonio; Puerta Notario, Antonio (My University, 2024)
This work presents an underwater optical wireless communications (UOWC) channel model, specifically addressing a non-Line-of-Sight (NLOS) configuration, accounting for the presence of a waving sea surface. Our model offers a com- prehensive deterministic analysis of the ocean wave impact, accurately determining the variable size of the beamwidth at the receiver plane reflected by the sea surface. Results confirm that oceanic wave variability induces severe misalignments in optical links, creating intermittent opportunities for effective communication. The optical-geometric analysis contributes sig- nificantly to understanding the novel impact of ocean waves on NLOS-UOWC systems. These findings enhance preliminary considerations in NLOS link design, particularly in scenarios with autonomous underwater vehicles in constant motion, aiding in reducing pointing errors.
Keywords: Comunicaciones ópticas; FSO; Comunicaciones subacuáticas